Investigating potential application of bio-based polymeric surfactant using methyl ester from palm oil for chemical enhanced oil recovery (CEOR) - Wibowo, Agam Duma Kalista; Megawati, Rizki; Setyaningrum, Vilia Kartika; Putri, Erika Wahyu; Joelianingsih; Handayani, Aniek Sri; Solikhah, Maharani Dewi; Chafidz, Achmad (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
Fatty Acid Methyl Ester (FAME) or palm oil methyl ester is one of the palm oil derivatives in which one of the anionic surfactants that can be generated from it is methyl ester sulfonate (MES). This bio-based surfactant can reduce the interfacial tension (IFT) between oil and water. To produce a bio-based polymeric surfactant, sulfonate groups from MES were grafted onto polymer chains. Palm oil methyl ester was reacted with sulfuric acid (H2SO4) to synthesize MES. Afterwards, MES was reacted with the Ethyl Acrylate (EA) monomer to synthesize polymeric surfactant. Investigating this route to produce a bio-based polymeric surfactant has become the novelty of this study. This study showed that the best polymerization result was obtained at a mole ratio of MES to EA (1:0.5) with the highest viscosity of 14.47 mm2/s. The critical micelle concentration (CMC) analysis showed 0.5% at a mole ratio of MES to EA (1:0.5) which corresponded to the lowest interfacial tension (IFT) of 1.95 x 10-3 mN/m. Meanwhile, the contact angle gradually decreased from 58.44 to 11.79°. The polymeric surfactant, furthermore, was analyzed using FTIR and H-NMR and successfully confirmed the formation of bio-based polymeric surfactant. The core flooding experiment found that approximately 16.57% of oil could be recovered. The results of the study revealed a good potential of the polymeric surfactant to be applied in chemical enhanced oil recovery (CEOR).